Essential Oils - Oils of Nature 2020
DOI: 10.5772/intechopen.87199
|View full text |Cite
|
Sign up to set email alerts
|

Study of Essential Oils Obtained from Tropical Plants Grown in Colombia

Abstract: Researchers from several Colombian universities have joined efforts for over 15 years to characterize the composition and biological properties of more than a thousand samples of essential oils (EOs) obtained from aromatic plants collected during at least 30 botanical outings in different regions of Colombia. This chapter presents a brief description of essential oil extraction and chemical characterization techniques, followed by a representative list of references to publications on EO composition obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…Existió actividad antifúngica por parte de los extractos acuosos evaluados frente a P. infestans en condiciones in vitro, por esta razón se consideraron como potenciales biofungicidas para el control de la enfermedad conocida como tizón tardío de la papa. Adicionalmente, es importante resaltar que la especie L. origanoides es una planta de fácil establecimiento que se encuentra en estado silvestre en el norte de Sur América y América Central (Stashenko & Martínez, 2019), la cual presenta una alta actividad biológica en varios campos de estudio y que se encuentra distribuida en varios departamentos de Colombia, sin embargo, este tipo de plantas requiere que se desarrollen planes para su producción masiva y estudios que permitan evaluar el comportamiento a nivel in planta y en campo para determinar su eficacia, fitotoxicidad y residualidad, con el fin de proponer productos adecuados para una producción limpia.…”
Section: Discussionunclassified
“…Existió actividad antifúngica por parte de los extractos acuosos evaluados frente a P. infestans en condiciones in vitro, por esta razón se consideraron como potenciales biofungicidas para el control de la enfermedad conocida como tizón tardío de la papa. Adicionalmente, es importante resaltar que la especie L. origanoides es una planta de fácil establecimiento que se encuentra en estado silvestre en el norte de Sur América y América Central (Stashenko & Martínez, 2019), la cual presenta una alta actividad biológica en varios campos de estudio y que se encuentra distribuida en varios departamentos de Colombia, sin embargo, este tipo de plantas requiere que se desarrollen planes para su producción masiva y estudios que permitan evaluar el comportamiento a nivel in planta y en campo para determinar su eficacia, fitotoxicidad y residualidad, con el fin de proponer productos adecuados para una producción limpia.…”
Section: Discussionunclassified
“…Many aromatic species from the Asteraceae, Annonaceae, Lamiaceae, Poaceae, Rutaceae, Verbenaceae, and Zingiberaceae families grown in Colombia have important potential for the discovery of biologically active substances [1,2], because they produce endogenous antioxidants necessary for the neutralization of reactive oxygen species (ROS), including phenolics, flavonoids, anthocyanidins and anthocyanins, phenylpropanoids, stilbenes, terpenes and terpenoids, steroids, lignans, carotenoids, and essential oils (EOs) [3][4][5]. All these compounds play a significant role as defense mechanisms against infections and as a means of survival in an adverse environmental climate, e.g., in an environment rich in solar radiation [6].…”
Section: Introductionmentioning
confidence: 99%
“…All these compounds play a significant role as defense mechanisms against infections and as a means of survival in an adverse environmental climate, e.g., in an environment rich in solar radiation [6]. Among the various plant-derived natural products, EOs are of great relevance because they can be used as active ingredients with health-improving properties when they are employed in the phytopharmaceutical and food industries [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colombia is the most biodiverse country in the world in proportion to its territorial area; a decade ago, it was considered that in the country there were around 50,000 plant species, however, recent studies have shown that the real range figures between 29,000 and 31,000 species [ 7 ]. Despite the richness of Colombian flora, a small number of species has been studied in order to discover their pharmacological characteristics and chemical composition [ 8 , 9 , 10 , 11 ]. Studies of natural products from plants have led to the discovery of widely used drugs, and it is considered that 52% of new molecules approved since 1981 for disease treatment are natural products or derived from these molecules [ 12 ].…”
Section: Introductionmentioning
confidence: 99%